The role of visual aids and multimedia in primary english education: a literature review - Nabila Syahara; Tiarnita Maria Sarjani Br Siregar; Suci Salsabila; Dwi Wulan Joy Tobing; Munisa Putri; Nursari Wahyuni Sigalingging (Indonesian Journal Education, 2026)
Teaching English at the primary school level is a foundational stage in developing pupils' language competence. However, students often struggle with vocabulary acquisition when taught through traditional, verbal-heavy methods. This study employs a qualitative literature review method to explore the role of visual aids and multimedia in enhancing English instruction. The analysis reveals that visual media, such as flashcards, posters, and realia, provide essential cognitive support by linking linguistic forms to concrete meanings. Furthermore, the integration of digital multimedia—including videos and interactive applications—significantly boosts student motivation, engagement, and oral communication skills. While digital tools offer authentic language exposure, their effectiveness depends on thoughtful instructional design, teacher competency, and adequate school infrastructure. The study concludes that a strategic combination of traditional visual aids and modern multimedia creates a more interactive and meaningful learning environment conducive to long-term vocabulary retention and 21st-century skill development.